2004
DOI: 10.1097/00007632-200405010-00003
|View full text |Cite
|
Sign up to set email alerts
|

Biologic Modification of Ligamentum Flavum Cells by Marker Gene Transfer and Recombinant Human Bone Morphogenetic Protein-2

Abstract: Human LF cells were found to be susceptible to adenovirus-mediated marker gene transfer, which offers the possibility of a new range of possible genetic modifications. In human LF cells, BMP-2 was found to markedly up-regulate the expression of osteogenic phenotypes and to induce bone nodule formation. The results of this study support the notion that biologically modified LF cells, i.e., LF cells treated with BMP-2, or with adenovirus-mediated BMP-2 cDNA gene transfer, may facilitate spinal fusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…BMP-2 promotes osteogenic differentiation, the matrix production and proliferation of spinal ligament cells both in the OPLL and in some non-OPLL cell lines, but stimulating effects on the OPLL cells are more significant [26,47]. Treatment with BMP-2 or adenovirus-mediated BMP-2 cDNA gene transfer, results in up-regulation of the expression of osteogenic phenotypes and bone nodule formation in human ligamentum flavum cells [59]. Therefore, BMP-2 may act as both an initiator and a promoter of the ossification.…”
Section: Bmpsmentioning
confidence: 99%
“…BMP-2 promotes osteogenic differentiation, the matrix production and proliferation of spinal ligament cells both in the OPLL and in some non-OPLL cell lines, but stimulating effects on the OPLL cells are more significant [26,47]. Treatment with BMP-2 or adenovirus-mediated BMP-2 cDNA gene transfer, results in up-regulation of the expression of osteogenic phenotypes and bone nodule formation in human ligamentum flavum cells [59]. Therefore, BMP-2 may act as both an initiator and a promoter of the ossification.…”
Section: Bmpsmentioning
confidence: 99%
“…Recombinant BMP-2 has been shown to enhance the osteoblastic characteristics of osteoblast-like cells, as well as ligament cells from the posterior longitudinal ligament and ligamentum flavum. [32][33][34][35][36] Histopathological studies have also found significant increase in expression of BMP-2 in the ossification area of OLF and OPLL. [37][38][39][40] So we next specifically focus on BMP-2 variants in TOLF patients.…”
Section: Discussionmentioning
confidence: 97%
“…14 Many authors have postulated that it derives broadly from mechanical stress, but other metabolic and genetic factors may also be of relevance. 3,10,11,[27][28][29][30][31][32] Histologically, the lesion often presents with degeneration and disorganization of elastic fibers. 12,25,26,33,34 Yoshida et al 33 and Yayama et al 12 have shown increased production of collagen fibers in the lesion.…”
Section: Discussionmentioning
confidence: 99%